THE INFLUENCE OF LEADERSHIP, COMMUNICATION, AND SPIRITUALITY ON ORGANIZATIONAL PERFORMANCE: CASE STUDY AT SKG INDONESIA KARATE SCHOOL - Hendratmoko; Mutiarawati, Elisabeth Vita (Jurnal Komunikasi dan Bisnis, 2023)
The purpose of this study is to analyze the influence of leadership, communication, and spirituality variables on organizational performance. This study uses a qualitative approach by conducting in-depth interviews with five respondents. The five respondents are active karate practitioners who hold a black belt. The results of this study prove that the variables of leadership, communication, and spirituality have a significant influence on organizational performance. The role of the communication variable as a common moderator of the relationship between leadership and spirituality variables on performance and the spirituality variable as a partial moderator of the relationship between communication and leadership variables on performance.